1992
DOI: 10.3354/meps091193
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of melanomacrophage centres (MMCs) in dab Limanda limanda along a pollution transect in the German Bight

Abstract: This study attempted to demonstrate whether an aspect of non-specd~c cellular immunity could be used as a n lnd~cator of f~s h health In populatlons of d a b Lllnanda limanda exposed along a pollut~on gradient Replicate samples of d a b spleens were o b t a~n e d durlng the Bremerhaven Workshop from a senes of stations along a transect in the German B~g h t H~stochem~cal techn~ques, to demonstrate the components of the pigmented materials w~t h l n melanomacrophage centres (MMCs) indicated varylng amounts of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
(13 reference statements)
5
19
0
Order By: Relevance
“…Decreasing MA activity, which was found to be correlated with residues of dieldrin in male flounder liver, was in most cases accompanied by a small macrophage aggregate area (Broeg, unpublished data). This is in agreement with studies of Bucke et al (1992) on dab spleen macrophages. In contrast, other studies showed contradicting results and found an increase in macrophage aggregate numbers in spleen and kidney following exposure to sewage sludge (Secombes et al 1991).…”
Section: Macrophage Activity Testsupporting
confidence: 93%
“…Decreasing MA activity, which was found to be correlated with residues of dieldrin in male flounder liver, was in most cases accompanied by a small macrophage aggregate area (Broeg, unpublished data). This is in agreement with studies of Bucke et al (1992) on dab spleen macrophages. In contrast, other studies showed contradicting results and found an increase in macrophage aggregate numbers in spleen and kidney following exposure to sewage sludge (Secombes et al 1991).…”
Section: Macrophage Activity Testsupporting
confidence: 93%
“…Kranz (1989) quantified splenic hemosiderin in the dab L. limanda, which was more commonly found in fish with ulcerous livers than in fish that had recovered from the ulcer disease. Also in the dab, Bucke et al (1992) found significantly reduced hemosiderin content at sites with the highest and the lowest levels of contaminated sediment; however, these authors recognized that the fish may have migrated between sites. Manual counting of MAs is potentially ambiguous in salmonids, depending on the definition of a MA, and is clearly time-consuming.…”
Section: Discussionmentioning
confidence: 90%
“…Splenic hemosiderin was quantified by Kranz (1989), Bucke et al (1992) and Khan & Nag (1993), and Mizuno et al (2002) quantified melanin in the kidney interstitium in masu salmon Oncorhynchus masou.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the view proposed by other studies that hemosiderin concentration can represent a useful tool for monitoring fish health (Bucke at at. 1984(Bucke at at. .…”
Section: A-collection Offish Samplesmentioning
confidence: 99%